tatistical study on the prevalence of the use of the Ephedra alata in the El-Oued region and Study of its protective effect on Bleomycin induced toxicity and oxidative stress in Albinos rats - Meriem, Chadou; Ouafa, Zouari Ahmed; Wissal, Ben Ghalia (جامعة الوادي - university of eloued, 2024)
The objective of this work was to do a statistical study on the prevalence of the use of the Ephedra alata in the El-Oued region and study the effect of aqueous extract of Ephedra alata L. for protection of toxicity induced by Bleomycin in rats. For statistical study, 5 persons interviewed were chosen; some of the informations related to the interrogators and others about the plant were adopted in the survry. For in-vitro study, qualitative and quantitative phytochemical compounds and biological activities were assess on the Ephedra alata L aqueous extract. For in-vivo study, Twenty female albino Wistar rats. were divided into 4 groups (n = 5); Control group, E. alata group (AEEA), Bleomycin group (BLM) and rats co-treated with BLM and AEEA group ( BLM+ AEEA). BLM induced toxicity using intraperitoneally single dose 10 U/kg. E. alata treated orally at a dose 200 mg/kg/day for 30 days. Various hematological, biochemical, and oxidative stress markers were estimated. Histopathology of liver, lungs and kidneys tissues was observed. The results obtained show that in traditional medicine, men and people between the ages of 31 and 60 years are more interested in using Ephedra alata. The aerial part of the plant is mostly used by decoction method to treat cancerous diseases and diabetes. Results of in-vitro phytochemical results revealed that E. alata contains most of active compounds, especially flavonoids of various kinds with high antioxidant and anti-inflammatory activity. Results of in-vivo rats study show that BLM treated rats induced alteration in Hematological and biochemical parameters compared to control group. Also BLM treated rats induced oxidative stress and histological alteration in lungs cells, liver and kidney compared to control rats. Co-treatment of BLM with AEEA were partially reversed all of previous parameters, Without any negative effect for the use of the plant in healthy rats. This study indicated that the anti-inflammatory and antioxidant property of leaves aqueous extract of Ephedra alata allowed to use them to protect organs from the side effects of drugs or from the destructive effects of various diseases. Other studies are necessary to delve into these findings and to determine the factors responsible for the beneficial effects of the plant.
Applied Biochemistry
Keywords: Ephedra alata L; Bloemycin; side effect; lungs; polyphenols; oxidative stress; Wistar rats.